Needle-free jet injector intradermal delivery of fractional dose inactivated poliovirus vaccine: Association between injection quality and immunogenicity. Issue 43 (26th October 2015) - Resik, Sonia; Tejeda, Alina; Mach, Ondrej; Sein, Carolyn; Molodecky, Natalie; Jarrahian, Courtney; Saganic, Laura; Zehrung, Darin; Fonseca, Magile; Diaz, Manuel; Alemany, Nilda; Garcia, Gloria; et al.
Abstract Introduction The World Health Organization recommends that as part of the polio end-game strategy a dose of inactivated poliovirus vaccine (IPV) be introduced by the end of 2015 in all countries currently using only oral poliovirus vaccine (OPV). Administration of fractional dose (1/5 of full dose) IPV (fIPV) by intradermal (ID) injection may reduce costs, but its conventional administration is with Bacillus Calmette-Guerin (BCG) needle and syringe (NS), which is time consuming and technically challenging. We compared injection quality achieved with BCG NS and three needle-free jet injectors and assessed ergonomic features of the injectors. Methods Children between 12 and 20 months of age who had previously received OPV were enrolled in the Camaguey, Cuba study. Subjects received a single fIPV dose administered intradermally with BCG NS or one of three needle-free injector devices: Bioject Biojector 2000® (B2000), Bioject ID Pen® (ID Pen), or PharmaJet Tropis® (Tropis). We measured bleb diameter and vaccine loss as indicators of ID injection quality, with desirable injection quality defined as bleb diameter ≥5 mm and vaccine loss <10%. We surveyed vaccinators to evaluate ergonomic features of the injectors. We further assessed the injection quality indicators as predictors of immune response, measured by increase in poliovirus neutralizing antibodies in blood between day 0 (pre-IPV) and 21 (post-vaccination). Results Delivery by BCG NS and Tropis resulted in the highest proportion of subjects with desirable injection quality; health workers ranked Biojector2000 and Tropis highest for ergonomic features. We observed that vaccine loss and desirable injection quality were associated with an immune response for poliovirus type 2 (P = 0.02, P = 0.01, respectively). Conclusions Our study demonstrated the feasibility of fIPV delivery using needle-free injector devices with high acceptability among health workers. We did not observe the indicators of injection quality to be uniformly associated with immune response.